2018
DOI: 10.1039/c7fo01435j
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fruits and arthritis

Abstract: Arthritis is a global health concern affecting a significant proportion of the population and associated with reduced quality of life. Among the different forms of arthritis, osteoarthritis (OA) and rheumatoid arthritis (RA) are the most common and lacking a definite cure in the affected individuals. Fruits, such as berries and pomegranates are rich sources of a variety of dietary bioactive compounds, especially the polyphenolic flavonoids that have been associated with antioxidant, anti-inflammatory and analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 48 publications
0
38
1
1
Order By: Relevance
“…Vitamin C (ascorbic acid) is well known for its effects on the immune system, and in states of increased inflammation, vitamin C levels tend to decrease in the body [52]. Several studies in cell, animals, and humans have suggested that red-colored foods and/or their isolated constituents [53] may assist with reducing systemic inflammation and bolstering immune status by reducing infections, including watermelon [54], apples [55][56][57][58][59][60][61], cherries [61][62][63], cranberries [57,64,65] pomegranate [66][67][68][69][70], and raspberries [71][72][73].…”
Section: Red Foods and Inflammationmentioning
confidence: 99%
“…Vitamin C (ascorbic acid) is well known for its effects on the immune system, and in states of increased inflammation, vitamin C levels tend to decrease in the body [52]. Several studies in cell, animals, and humans have suggested that red-colored foods and/or their isolated constituents [53] may assist with reducing systemic inflammation and bolstering immune status by reducing infections, including watermelon [54], apples [55][56][57][58][59][60][61], cherries [61][62][63], cranberries [57,64,65] pomegranate [66][67][68][69][70], and raspberries [71][72][73].…”
Section: Red Foods and Inflammationmentioning
confidence: 99%
“…In China, the LDS series moisture detector manufactured by Shanghai Qingpu Oasis Detection Instrument Co., Ltd. adopts a structure of coaxial cylindrical capacitance sensor, which has poor repeatability and low accuracy when measuring the moisture content of peanuts; The GMK-303U grain moisture detector manufactured by G-won company of Korea can measure the moisture content of peanut kernel in the range of 4.8%-14.7%, with an accuracy of ± 0.5%. The PM8188 type of capacitive moisture detector in Japan can be used to detect the peanut kernel samples with moisture content of 4%-15% (Basu et al, 2018;Taki et al, 2018). The instrument is easy to operate, but the measurement results error of some samples are as high as 2%-3% compared with the standard drying method.…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 99%
“…The benefits of dark chocolate have been attributed to a type of polyphenols known as flavonoids, which include flavonols and other polyphenols, such as epicatechin and catechin. In this line, some studies [ 14 ] have related the consumption of certain flavonol- and polyphenol-rich products, such as propolis [ 15 ], fruits and vegetables [ 16 ], to QoL, with rather inconclusive results. In women, the habitual consumption of coffee has been associated with slight improvement in the mental dimension of QoL [ 17 ].…”
Section: Introductionmentioning
confidence: 99%